The Effect of Variations in Induction Tube Volume and Membrane Thickness on the Performance of A 150 CC 2-Stroke Motorcycle - gusti, gusti; Monasari, Ratna; Firdaus, Hanif (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
One of the efforts to improve the performance of a gasoline motor with a 2-stroke system is to make some modifications to the combustion system components. By changing the volume of the induction tube and the thickness of the membrane the performance of a 2-stroke gasoline motor can be improved from standard conditions. The purpose of this study is to understand how changes in the volume of the induction tube affect the performance of a 2-stroke motor engine with a capacity of 150 cc, with the aim of restoring optimal performance to the motor. This study uses an experimental method on how the effect of variations in induction tube volume and membrane thickness on gasoline motor performance. The test variable in the study is to compare 3 induction tube volumes and 2 membrane thicknesses to the resulting engine performance. Tests were carried out on a 150cc 2-stroke gasoline motor using a chassis dynamometer as a tool to see the performance of the test engine and a gas analyzer as a tool to measure the level of exhaust emissions produced. From the tests that have been carried out, it shows that the volume of the induction tube and the thickness of the membrane have an influence on the performance of a 150 cc 2-stroke gasoline motor. The highest torque is obtained on a 300cc induction tube with a membrane thickness of 0.45 mm of 19.60 Nm at 9,000 rpm. While for fuel consumption using the calculation of specific fuel consumption (SFC) obtained results of 0.08 g / kW.h. for exhaust emissions on HC produced at 2452 ppm and 0.97% on CO gas.